Liberia : Eighth Review Under the Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses key findings of the Eighth Review under the Extended Credit Facility for Liberia. Economic activity in Liberia remains on a solid upward trend. Inflation has nudged higher owing to rising international fuel prices and elevated food prices. The authorities' immediate fiscal priorities are to contain discretionary current spending and bolster investment. All performance criteria and indicative targets under the program through December 2011 were observed. One structural benchmark for the Eighth Review was met while the other is in progress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet